2018
DOI: 10.1155/2018/9139683
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis and Electrical Efficiency Improvement of a Hybrid PV/T Panel Cooled by Forced Air Circulation

Abstract: The thermal and electrical efficiency of a custom-designed PV/T panel cooled by forced air circulation was investigated by experimental and computational fluid dynamics (CFD) analysis. Experiments were carried out with four different array configurations, under constant irradiation of 1100 W/m2 and 3 different air velocities (3.3 m/s, 3.9 m/s, and 4.5 m/s). The heat transfer surface area and forced air circulation are known to positively affect the total heat transfer, and therefore, it is foreseeable that an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As a result, the average temperature of PV panels with heat sinks was lower than in PV panels without heat sinks. Research by Omeroglu [36] revealed a similar result where the heat sink configuration affected the air velocity and heat transfer rate from a PV panel to the surrounding environment. Popovici et al [23] demonstrated that the orientation and direction of the fin in the heat sink also affected the air temperature distribution.…”
mentioning
confidence: 78%
“…As a result, the average temperature of PV panels with heat sinks was lower than in PV panels without heat sinks. Research by Omeroglu [36] revealed a similar result where the heat sink configuration affected the air velocity and heat transfer rate from a PV panel to the surrounding environment. Popovici et al [23] demonstrated that the orientation and direction of the fin in the heat sink also affected the air temperature distribution.…”
mentioning
confidence: 78%
“…Blasius equation for Turbulent Friction factor in smooth circular pipe is denoted by Eq. ( 11) and the same referred in Omeroglu [19] and Deng et al [25].…”
Section: Q Input = Vi: ð2þmentioning
confidence: 71%
“…Nusselt number ratio used by Omeroglu [19] and Deng et al [25] for evaluating the augmentation is represented in Nu Nu o : ð9Þ…”
Section: Q Input = Vi: ð2þmentioning
confidence: 99%
See 2 more Smart Citations